Direct determination of failure surfaces in earth slopes - S. L. Huang (International Conference on Ground Control in Mining, 1989)
The location and shape of potential failure surfaces in soil slopes were directly determined based on the stresses induced in the soil mass and the strength of the soil itself. Stress calculations were carried out by the finite element method with the Drucker-Prager nonlinear material model. The Mohr-Coulomb failure criterion and Mohr's circle stress analysis were then applied to the calculated stresses to determine the characteristics of the failure surface.